Effect of different habitat types on abundance and biting times of Anopheles balabacensis Baisas (Diptera: Culicidae) in Kudat district of Sabah, Malaysia - Tock Hing Chua; Benny O. Manin; Indra Vythilingam; Kimberly Fornace; Chris J. Drakeley (BioMed Central, 2019)
We investigated the effect of five common habitat types on the diversity and abundance of Anopheles spp. and on the biting rate and time of Anopheles balabacensis (currently the only known vector for Plasmodium knowlesi in Sabah) at Paradason village, Kudat, Sabah. The habitats were forest edge, playground area, longhouse, oil palm plantation and shrub-bushes area. Sampling of Anopheles was done monthly using the human landing catch method in all habitat types for 14 months (October 2013 to December 2014, excluding June 2014). The Anopheles species were morphologically identified and subjected to PCR assay for the detection of Plasmodium parasites. Generalised linear mixed models (GLMM) were applied to test the variation in abundance and biting rates of An. balabacensis in different habitat types. A total of 1599 Anopheles specimens were collected in the village, of which about 90% were An. balabacensis. Anopheles balabacensis was present throughout the year and was the dominant Anopheles species in all habitat types. The shrub bushes habitat had the highest Anopheles species diversity while forest edge had the greatest number of Anopheles individuals caught. GLMM analysis indicated that An. balabacensis abundance was not affected by the type of habitats, and it was more active during the early and late night compared to predawn and dawn. PCR assay showed that 1.61% of the tested An. balabacensis were positive for malaria parasites, most of which were caught in oil palm estates and infected with one to two Plasmodium species. The identification of infected vectors in a range of habitats, including agricultural and farming areas, illustrates the potential for humans to be exposed to P. knowlesi outside forested areas. This finding contributes to a growing body of evidence implicating environmental changes due to deforestation, expansion of agricultural and farming areas, and development of human settlements near to forest fringes in the emergence of P. knowlesi in Sabah.